Personality Of Malala Reflected In Malala Yousafzai & Christina Lamb's I Am Malala (2013) Memoir: A Psychoanalytic Approach - Novyanti, Caecilia Tiewuk, Dr. Phil. Dewi Chandraningrum, M. Ed, Titis Setyabudi, S.S. M. Hum (2015)
The major problem in this study is how personality of Malala is reflected in "I am Malala" memoir. The objectives of this study is to analyze I am Malala (2013) memoir based on psychoanalytic approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source is about the novel itself. Then, the secondary data sources are the books about psychoanalysis, references from internet about I Am Malala, and other sources, which have relation to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the analysis, the writer get some conclusions. The study shows that the problem faced by the major character is her own personality who can influence other people especially women in the world about the important of education. It is proved by she became a global symbol of peaceful protect and the youngest nominee ever for the Nobel Peace Prize. The role of parents, religion, teachers, lectures and good society however is really important for teenager development. Keywords: Personality, Frustation, Id, Ego, Superego.